Innate Immune Response Regulation by the Human RNASET2 Tumor Suppressor Gene - Acquati, Francesco; Mortara, Lorenzo; De Vito, Annarosaria; Baci, Denisa; Albini, Adriana; Cippitelli, Marco; Taramelli, Roberto; Noonan, Douglas M. (Frontiers in Immunology, 2019)
The link between cancer development or progression and immune system dysregulation has long been established. Virtually every cell type belonging to both the innate and adaptive immune system has been reported to be involved in a complex interplay that might culminate into either a pro- or anti-tumorigenic response. Among the cellular components of the innate immune system, cells belonging to the monocyte/macrophage lineage have been consistently shown to play a key role in the tumorigenic process. The most advanced human tumors are reported to be strongly infiltrated with Tumor-Associated Macrophages (TAMs) endowed with the ability to contribute to tumor growth and dissemination. However, given their widely acknowledged functional plasticity, macrophages can display anti-tumor properties as well. Based on these premises, experimental approaches to promote the in vivo macrophage shift from pro-tumor to anti-tumor phenotype represent one of the most promising research field aimed at developing immune system-mediated tumor suppressive therapies. In this context, the human RNASET2 oncosuppressor gene has emerged as a potential tool for macrophage-mediated tumor suppression. A growing body of experimental evidence has been reported to suggest a role for this gene in the regulation of macrophage activity in both in vitro and in vivo experimental models. Moreover, several recent reports suggest a role for this gene in a broad range of cell types involved in immune response, pointing at RNASET2 as a putative regulator of several functional features within the immune system.